2000
DOI: 10.1038/79728
|View full text |Cite|
|
Sign up to set email alerts
|

Crystal structure of a T cell receptor bound to an allogeneic MHC molecule

Abstract: Many T cell receptors (TCRs) that are selected to respond to foreign peptide antigens bound to self major histocompatibility complex (MHC) molecules are also reactive with allelic variants of self-MHC molecules. This property, termed alloreactivity, causes graft rejection and graft-versus-host disease. The structural features of alloreactivity have yet to be defined. We now present a basis for this cross-reactivity, elucidated by the crystal structure of a complex involving the BM3.3 TCR and a naturally proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
154
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(161 citation statements)
references
References 37 publications
6
154
1
Order By: Relevance
“…Although alloreactive T cells can recognize structural determinants of the foreign MHC molecules independent of the bound peptides (5)(6)(7), it has become clear that, for most alloreactive T cells, recognition depends on peptides within the allo-MHC groove (5,6,8,9). Structural studies on alloreactive TCR complexed with allogeneic MHC molecules have confirmed the role played by peptides in alloreactivity (10,11). As originally proposed by Matzinger and Bevan (12), it thus appears that alloreactive TCRs exploit the similarities, rather than the differences, between the top of the helices of self-and allo-MHC molecules.…”
mentioning
confidence: 92%
“…Although alloreactive T cells can recognize structural determinants of the foreign MHC molecules independent of the bound peptides (5)(6)(7), it has become clear that, for most alloreactive T cells, recognition depends on peptides within the allo-MHC groove (5,6,8,9). Structural studies on alloreactive TCR complexed with allogeneic MHC molecules have confirmed the role played by peptides in alloreactivity (10,11). As originally proposed by Matzinger and Bevan (12), it thus appears that alloreactive TCRs exploit the similarities, rather than the differences, between the top of the helices of self-and allo-MHC molecules.…”
mentioning
confidence: 92%
“…On the molecular level, the corollary of this hypothesis is that a TCR clonotype will exhibit sufficient intrinsic conformational diversity to crossreact with several molecular mimics and less structurally related pMHCI complexes (51)(52)(53). Although alloreactive and/or xenoreactive ligands have been identified for other TCRs (51,(53)(54)(55)(56), few cross-reactive syngeneic interactions between naturally occurring pMHCI and cognate TCR have been identified (57)(58)(59)(60). Indeed, to the best of our knowledge, this study is the first to characterize the interaction between a pathogen-reactive human TCR and a cross-reactive self-peptide in biophysical terms.…”
Section: Functional Optimization Of Soluble Tcrsmentioning
confidence: 99%
“…However, at least some V-gene segments can use more than one set of interactions to bind a given MHC molecule. For example, two Vb2-containing TCRs with different peptide specificities show distinct docking footprints on the H-2K b a1 helix (Reiser et al 2000;Reiser et al 2003). The hypervariable CDR3 loops of the TCR and …”
Section: Structural Insights Into the Mechanism Of Mhc Restrictionmentioning
confidence: 99%